Distal Renal Tubular Acidosis: Clinical Variability in the Same Family - Ramos, Daniela (2019)
Primary distal renal tubular acidosis is a genetic disorder characterized by the inability in acidification of urine. Symptoms are usually non-specific and highly variable. We described six cases in a family with four generations affected. The first case was diagnosed in a 3-year-old child presenting with hematuria and urolithiasis. Later, his sister, sons and two nephews were studied. Although asymptomatic, they all had nephrocalcinosis and hyperchloremic metabolic acidosis with normal anionic gap, except one case with normal arterial blood gas test but with nephrocalcinosis and inability of urinary acidification. At follow-up, they all maintained nephrocalcinosis, the index case had acute renal damage and developed hypertension, but none developed chronic renal disease. The diagnosis of autosomal dominant distal renal tubular acidosis is generally made later and patients tend to present with milder disease. But the condition may manifest early and have a variable phenotypic severity spectrum. Carrying out screening through assessment of family history enables an earlier diagnosis while also allowing treatment to start sooner.